PENGARUH PEMBERIAN EKSTRAK AIR DAUN KATUK (Sauropus androgynus) DAN DAUN KELOR (Moringa oleifera Lam) PADA AIR MINUM TERHADAP BERAT POTONG DAN BERAT KARKAS AYAM PEDAGING - I K. A., Kurniawan; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 5 No 1 (2017), 2017)
The purpose this study was to assess the provision of 5% water extract of leaves katuk (Sauropus androgynus) and the water extract of leaves of Moringa (Moringa aloivera Lam) in drinking water can increase the weight of beef and broiler chicken carcasses. The design used in this study is completely randomized design (CRD) with three treatments and six replications. These three treatments are chickens given drinking water without the water extract of leaves of Moringa or katuk as control (A), chicken by water extract of leaves katuk 5% through drinking water (B), Chicken by water extract of leaves of Moringa 5% through drinking water (C). The variables measured were: slaughter weight, carcass weight, carcass percentage, the consumption of protein and lysine consumption. The results showed that pieces of broilers fed extracts of leaves katuk 5% water through drinking water (B) and broilers were given a water extract of leaves of Moringa 5% through drinking water (C), respectively 17,47% and 17,20% were significantly different (P<0.05) higher than the untreated A. chicken carcass weight of broilers were treated (B) and broilers are treated (C), respectively 25,62% and 25,16% were significantly different (P<0.05) than chickens treated A. Percentage of broiler carcasses were treated B and broilers are treated C, respectively 6,95% and 6,79% were significantly different (P<0.05) higher compared to treatment A. protein consumption of broilers were treated B and broilers are treated C, respectively 2,03% and 1,80% were significantly different (P<0.05) higher compared to the treatment of A. and the consumption of lysine broilers were treated B and broilers are treated C, respectively 1,87% and 1,77% were significantly different (P<0.05) higher in comparison with treatment A. Based this study it can be concluded that the provision of 5% of katuk leaves (Sauropus androgynus) and/or Moringa leaves (Moringa aloivera Lam) water extract in drinking water can increase the slaughter weight and carcasses of broiler.
Keywords: katuk leaves, moringa leaf, and broilers